Complication related to colostomy orifice: intestinal evisceration - Salles,Valdemir José Alegre (2011)
Intestinal evisceration at the site of a stoma is a rare event, with high morbimortality. Its clinical manifestation often occurs between the sixth and seventh days after surgery. The risk factors most frequently related to evisceration are: increased intra-abdominal pressure, digestive tract cancer surgery, emergency surgery and stomas in the surgical incision. The authors report the case of a male patient, aged 62, suffering from adenocarcinoma of the rectum with obstructive acute abdomen, who underwent loop transversotomy for decompression. On the fourth day after surgery, he had a bronchospasm crisis, with evisceration of ileum and colon through the colostomic hole. The association of some triggering factors, such as emergency surgery, colorectal malignant neoplasm, increased intra-abdominal pressure and technical failure of colostomy were decisive in the development of this rare peri-colostomy complication.